Refugee Caregivers' Perceptions of Using Mindfulness-Based Interventions to Support Coping Skills in Children with Disability in Jordan - Zeina Fayad; Hadeel R. Bakhsh; Rawan AlHeresh (MDPI AG, 2024)
Background: Refugee children with disabilities are vulnerable to developing dysfunctional coping skills due to barriers in accessing health care services, including occupational therapy (OT). This study investigated the perceptions of refugee caregivers regarding the use of mindfulness-based interventions (MBIs) as a treatment for coping skills among their children with disabilities. Methods: A qualitative survey was used to analyse the coping mechanisms and access to services among refugee children with disabilities, as well as their caregivers' perceptions regarding the use of MBIs. The caregivers were recruited using convenience sampling from a database of individuals at the Al-Baqa'a refugee camp in Jordan via their community-based rehabilitation (CBR) centre. A demographic survey was sent to 156 refugees using WhatsApp. Refugees above the age of 18 years identifying as the caregivers of children with disabilities were eligible. Twenty-eight individuals completed the survey, and twenty-six were eligible. Open-ended questions asked about their child's struggles, supports, barriers to support, and perceptions of MBIs. The data were collected via Google Sheets. Three researchers coded the responses using a descriptive coding method and line-by-line analysis. Results: Five themes were derived from the responses: "Daily Challenges", "Support and Strategies", "barriers to accessing support", "MBIs: Caregiver Perceptions", and "MBIs: Barriers". The participants identified the behavioural, emotional, and cognitive challenges impacting their child's participation. Financial and environmental constraints, stigma, and timing were the reported barriers to services. The participants felt positive about the potential of MBIs to support their children. Conclusions: Overall, this study obtained foundational data to establish accessible mental health programmes for refugees with disabilities. Further research is needed to transcend the barriers and maintain MBI programmes in the community and the home settings.